Data Management and Preservation Planning for Big Science - Juan Bicarregui; Norman Gray; Rob Henderson; Roger Jones; Simon Lambert; Brian Matthews (International Journal of Digital Curation, 2013)
‘Big Science’ - that is, science which involves large collaborations with dedicated facilities, and involving large data volumes and multinational investments – is often seen as different when it comes to data management and preservation planning. Big Science handles its data differently from other disciplines and has data management problems that are qualitatively different from other disciplines. In part, these differences arise from the quantities of data involved, but possibly more importantly from the cultural, organisational and technical distinctiveness of these academic cultures. Consequently, the data management systems are typically and rationally bespoke, but this means that the planning for data management and preservation (DMP) must also be bespoke.